Tandospirone, a 5-HT1A partial agonist, ameliorates aberrant lactate production in the prefrontal cortex of rats exposed to blockade of N-methy-D-aspartate receptors; Toward the therapeutics of cognitive impairment of schizophrenia - Uehara, Takashi; Matsuoka, Tadasu; Sumiyoshi, Tomiki (Frontiers in Behavioral Neuroscience, 2014)
Rationale: Augmentation therapy with serotonin-1A (5-HT1A) receptor partial agonists has been suggested to improve cognitive impairment in patients with schizophrenia. Decreased activity of prefrontal cortex may provide a basis for cognitive deficits of the disease. Lactate plays a significant role in the supply of energy to the brain, and glutamatergic neurotransmission contributes to lactate production. Objectives and methods: The purposes of this study were to examine the effect of repeated administration (once a daily for 4 days) of tandospirone (0.05 or 5 mg/kg) on brain energy metabolism, as represented by extracellular lactate concentration (eLAC) in the medial prefrontal cortex (mPFC) of a rat model of schizophrenia. Results: Four-day treatment with MK-801, an NMDA-R antagonist, prolonged eLAC elevation induced by foot-shock stress (FS). Co-administration with the high-dose tandospirone suppressed prolonged FS-induced eLAC elevation in rats receiving MK-801, whereas tandospirone by itself did not affected eLAC increment. Conclusions: These results suggest that stimulation of 5-HT1A receptors ameliorates abnormalities of energy metabolism in the mPFC due to blockade of NMDA receptors. These findings provide a possible mechanism, based on brain energy metabolism, by which 5-HT1A agonism improve cognitive impairment of schizophrenia and related disorders.